Achalasia During Pregnancy: Proposed Management Algorithm Based on a Thorough Literature Review - Vosko, Sergei; Cohen, Daniel L; Neeman, Ortal; Matalon, Shai; Broide, Efrat; Shirin, Haim (Journal of neurogastroenterology and motility, 2021)
Fewer than 40 cases of achalasia occurring in pregnant woman have been reported in the literature. Given the rarity of achalasia during pregnancy, and the numerous treatment options that are available for achalasia in general, no guidelines exist for the management of achalasia during pregnancy. Diagnosis of new cases may be difficult as symptoms and physiological changes that occur during pregnancy may obscure the clinical presentation of achalasia. The management of achalasia in pregnancy is also challenging. Treatment decisions should be individualized for each case, considering both the welfare of the mother and the fetus. Since pregnant women suffering from achalasia represent a diagnostic and therapeutic challenge with complex maternal-fetal aspects to consider, we have reviewed the available literature on the subject and summarized current diagnostic and therapeutic options. Additionally, we present a management algorithm as a means to guide treatment of future cases. We recommend that a conservative approach should be adopted with bridging therapies performed until after delivery when definitive treatment of achalasia can be more safely performed.